Head's Leadership Styles and Effectiveness of School Teams: Exploring the Role of Motivational Mechanisms - Allah Wasaya Anjum; Riffat un Nisa Awan; Muhammad Zulqarnain (National University of Modern Languages (NUML), Islamabad, 2021)
The literature reveals that participative leadership style (PLS) is overwhelmingly advantageous over the contrasting directive leadership style (DLS). Therefore, the key objective of this study was to find out the relative effect of a PL style as compared to a DL style on the  motivational mechanism (organizational commitment and empowerment) and effectiveness (innovation and in-role performance) of school staff teams. However, the mediating role of motivational mechanism in the relationship between school heads' leadership styles and effectiveness of school staff teams had also been studied. The data were collected through a questionnaire based cross-sectional survey. The data were collected from the 402 teachers working in 80 academic teams. The SEM results revealed that DLS was significantly related to teams' in-role performance and organizational commitment. While, PLS was significantly related to in-role performance, team's innovation, organizational commitment and personal empowerment. Teachers' personal empowerment partially mediated the relationship between heads' PLS and team innovation. But, organizational commitment fully mediated the relationship between heads' PLS and teams' in-role performance. However, organizational commitment partially mediated the relationship between heads' DLS and teams' in-role performance. It is suggested that heads might concurrently combine participative and directive leadership behaviors to make their school teams more effective.